1972
DOI: 10.1017/s0021859600087839
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into copper deficiency in cattle in the Southern Pennines. I. Identification of suspect areas using geochemical reconnaissance followed by blood copper surveys

Abstract: SUMMARYSevere clinical copper deficiency has been recognized for some years on a number of farms within an area of 10 square miles in North Staffordshire. Response to injected copper is good and supplementation is now regular practice. One of the causes would appear to be a dietary excess of molybdenum, confirmed in soil and pasture.Geochemical reconnaissance in 1965 delineated areas totalling 60 square miles, including the above area, in which molybdenum occurs in above normal concentrations in stream sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to these results silage-fed animals may become deficient in Cu since the values for the silagc-fed groups were bclow those defined as indicating a deficiency (Thornton et al 1972) whereas those fed hay maintained plasma copper levels within the normal range. Hartmans and Bosman (1970) (Miltimore et al 1970), or where grass silages form the basis of the rations, or in both arcas.…”
Section: Generalmentioning
confidence: 84%
“…According to these results silage-fed animals may become deficient in Cu since the values for the silagc-fed groups were bclow those defined as indicating a deficiency (Thornton et al 1972) whereas those fed hay maintained plasma copper levels within the normal range. Hartmans and Bosman (1970) (Miltimore et al 1970), or where grass silages form the basis of the rations, or in both arcas.…”
Section: Generalmentioning
confidence: 84%
“…In Derbyshire, Mo anomalies in stream sediment led to the recognition of areas totalling some 150 km2 in which over 75 % of the cattle were hypocupraemic but showed no clinical signs of hypocuprosis (Thornton et al 1972). Subsequent Cu supplementati responses in live-weight gain in young cattle ranging from 14 to 32 kg per animal over a grazing season of 6 months.…”
Section: Thornton and Webb Platementioning
confidence: 99%
“…Dick therefore concluded that inorganic SO, was the additional factor involved in the Cu-Mo antagonism. In recent field and experimental studies of the Cu-Mo-sulphur interrelationship in ruminant nutrition, emphasis was also given to the inorganic S component in the ruminant diet (Bingley & Anderson, 1972;Thornton, Kershaw & Davies, 1972;Todd, 1972). Further evidence that SO, is still considered to be the crucial third factor in the interaction is evident from the recent review by Underwood (1972).…”
mentioning
confidence: 99%